Needs analysis is the procedure for collecting information about learners` needs and it is essential in determining, materials, teaching activities, tests, evaluation strategies and reevaluating them. The aims of this research was analyze the students nee - Nurhidayat Nurhidayat (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2017)
Needs analysis is the procedure for collecting information about learners` needs and it is essential in determining, materials, teaching activities, tests, evaluation strategies and reevaluating them. The aims of this research was analyze the students needs writing skill in learning English subject and selecting material to teaching. This research was descriptive research in which questionnaire was distributed to students to obtain more accurate information on students needs. The data analyzed in quantitative and qualitative methods. The findings of this research revealed of analysis indicate that the students’ level of all writing components ranges around level “fair” as average score. The teaching of English especially writing skills particularly on students Academy Health Analyst Muhammadiyah Makassar needs to get more serious handling to help students to express and expose their idea in writing by developing the students’ vocabulary, grammar, and mechanism and prepare students have good basic in writing especially in formal writing.